ASSISTANCE IN IMPROVING READING SKILLS FOR CHILDREN AT TUNAS BAHAGIA FOUNDATION LUWUK GUNUNG SARI SERANG - Fachrurozi, Khalid Nur; Anggraeni, Lucky Zenny; Mahmudah, Mita Laili; Kusuma, Jaka Wijaya; Hamidah, Hamidah; Marlina, Mira (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
Community service is an activity that aims to help a specific community in several activities without expecting anything in return. In general, this program is designed by various universities or institutes in Indonesia to make a real contribution to the Indonesian nation, especially in developing the welfare and progress of the Indonesian nation. Community Service activities are one part of the Tri Dharma of Higher Education. The Covid-19 pandemic has impacted the implementation of community service programs. The community service location is Wates village RT 04 RW 02 Luwuk Village, Gunung Sari District, Serang Regency, Banten Province, Indonesia. This community service work program aims to  provide education to the people of Luwuk village, especially  the children of Wates village, by teaching reading